Becoming a Mother During COVID-19 Pandemic: How to Protect Maternal Mental Health Against Stress Factors - Bottemanne, Hugo; Vahdat, Brune; Jouault, Cleo; Tibi, Ruben; Joly, Lucie (Frontiers in Psychiatry, 2022)
During the COVID-19 pandemic, there were an increasing prevalence of perinatal psychiatric symptoms, such as perinatal anxiety, depression, and post-traumatic stress disorders. This growth could be caused by a range of direct and indirect stress factors related to the virus and changes in health, social and economic organization. In this review, we explore the impact of COVID-19 pandemic on perinatal mental health, and propose a range of hypothesis about their etiological mechanisms. We suggest first that the fear of being infected or infected others (intrauterine transmission, passage of the virus from mother to baby during childbirth, infection through breast milk), and the uncertainty about the effect of the virus on the fetuses and infants may have played a key-role to weakening the mental health of mothers. We also highlight that public health policies such as lockdown, limiting prenatal visits, social distancing measures, and their many associated socio-economic consequences (unemployment, loss of income, and domestic violence) may have been an additional challenge for perinatal mental health. Ground on these hypotheses, we finally purpose some recommendations to protect perinatal mental health during a pandemic, including a range of specific support based on digital technologies (video consultations, phone applications) during pregnancy and the postpartum period.